Predictor of Mortality in Patients Undergoing Urgent Versus Planned Dialysis. A Study from DHQ Hospital, Faisalabad - Muhammad Usman, Yasir Hussain, Salman Shakoor (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Outcomes for urgent versus planned dialysis patients vary according to the literature. The current study aims to study the clinical outcomes of patients undergoing urgent dialysis compared to planned dialysis in a single center at the nephrology department of the DHQ hospital in Faisalabad. Methodology: In this analysis we selected sixty patients who meet the inclusion criteria from September 2019 to September 2021 and further divided the selected patients into two groups. The urgent dialysis group (Group UD) and the Planned dialysis group (Group PD) according to the pre-defined criteria. Each group had the equal number of age and sexed match patients (thirty patients each group). The follow up period after the initiation of dialysis was six months. The co morbid conditions, laboratory parameters and deaths in six months follow up period was noted in both groups. Results: The mean age in Group UD was 57.5 years and in Group PD was 62.5 years. The male in Group UD was 21 as compared to group PD consisted of 19 males (p=0.17). The most common cause of urgent renal dialysis was found to be volume overload (52%). The UD group did not have the history of proper nephrologist consultation and zero percent of participant had AV fistula at the time of first dialysis. During the follow-up period, there was significantly higher death rate in Group UD as compared to the Group PD (43.3% versus 26.6%, p= 0.003). The urgent initiation group had considerably lower levels of albumin, hemoglobin, and hematocrit but significantly greater levels of phosphorus and C-reactive protein. Multivariable logistic regression analysis found urgent dialysis initiation to be an independent risk factor for survival (HR 2.96; 95% CL 1.48–4.64; P = 0.01). Similarly, the older age, lower albumin, elevated levels of CRP and absences of vascular access were also found the significant predictor of mortality. Conclusion: Based on the results of our study we can conclude the urgent initial of dialysis may be the independent risk factor for one year mortality along with older age, higher CRP, and lower albumin levels. we also noted that the lack of nephology care and volume overload was the main reason of urgent dialysis. Keywords: Urgent Dialysis, mortality, Risk factors, hemodialysis, end stage renal disease.